KRITIK NARASI MISOGINIS: Analisis Pemikiran Fatima Mernissi tentang Hadis dan Kuasa Perempuan - Millat Ahmad, Nehru; Anam, Saichul; Rohadatul Aisyi, Hithna (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
This study examines Fatima Mernissi's thoughts on misogynistic hadiths and their relevance to women's leadership in the context of Islam. Mernissi, as a feminist thinker, challenged traditional interpretations of hadith that were considered degrading to women, as she stated in her book